Peran Pemerintah Dalam Proses Pemberian Bantuan Hukum secara Prodeo - Meilisa Naiborhu; Fauza Az-Zahra Jambak; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Based on the Advocate Law, one form of legal services provided by advocates is legal aid (Article 1 number 2 of the Advocate Law). The role of OBH in providing free legal assistance (Prodeo) to people/groups who are unable to process criminal cases is also stipulated in the Criminal Procedure Code. For people who cannot participate in the criminal justice system in certain cases, the officials concerned at all levels of examination are obliged to appoint legal advisers for them. This study uses normative juridical research. The type of data used in this study uses secondary data, namely data from library research. The results of this study are, in the midst of society, the less able groups are separated from the rich/capable groups. To overcome this injustice, the government seeks free legal assistance to people who cannot afford these legal services in order to achieve social justice for all Indonesian people, especially justice in the field of law. In practice, the interest of advocates to carry out the obligation to provide free legal aid and reporting is still low. Kata Kunci: Role of Government, Advocate, Legal Aid